Supraorbital Blowin Fracture Presenting as an Ocular Dystopia in a Nine-Year-Old Girl - Ranganadh Nallamothu; Shanmukha Reddy Kallam; Srikanth Gunturu; Sukumar Singh; Vijay Kumar Rachalapally (Case Reports in Dentistry)
A 9-year-old girl was referred to a trauma centre with severe head injury. 3D CT scan revealed depressed fracture involving the frontal bone on the right side, right parietal bone, and right superior orbital margin, right lamina papyracea. The frontal table was managed conservatively and open reduction and internal fixation was done for the supraorbital blow in to correct the ocular dystopia. The clinical course, possible mechanism, and management of the patient are discussed.